Mothers' perspectives of co-occurring fatigue in children with autism spectrum disorders. Issue 4 (2nd October 2021) - Keville, S.; Meek, C.; Ludlow, A. K.
ABSTRACT: Background: Fatigue seems deeply associated with Autism Spectrum Disorders (ASD) as reflected by the preferred terms 'autistic fatigue' and 'autistic burnout'. In ASD there is also a greater prevalence of sensory and cognitive demands, and medical conditions where persistent fatigue can be a symptom. This may contribute to some of the debilitating levels of fatigue evidenced, impacting on children with ASD and families. Objective: As parents caring for a child with ASD experience high levels of stress this study aimed to provide a deeper understanding of the lived experiences of parenting a child with ASD with co-occurring fatigue. Design: An interpretative phenomenological analysis was used to analyse semi-structured interviews from six mothers of children with ASD aged 4–19 who also had severe levels of co-occurring fatigue. Results: Four superordinate themes were generated: The experience of fatigue; Making sense of their child's fatigue; Managing fatigue; Accepting needs and limitations. Mothers developed understanding of their child's fatigue, guiding their child to self-regulate. As mismanagement increased meltdowns and emotional outbursts, managing fatigue was perceived to be a key aspect of living with the phenomenon. Conclusion: The findings reflect the impact of extreme fatigue on a child with ASD and families, supporting recent recommendations which state managing energy levels and reducing stressors is essential to prevent burnout in those with ASD and co-occurring fatigue. Better understanding, recognition and diagnosis would support parents, as would greater flexibility in schools to help children with ASD to better manage the demands of the school day.